CERITA RAKYAT SENTANI SEBAGAI MEDIA PENGEMBANGAN KARAKTER ANAK - Wigati Yektiningtyas; Raymond Fatubun (LPPM Uncen, 2021)
Sentani, Jayapura has various cultural heritages. One of them is folktale with some genres i.e. myths, legends, fables, and fairy tales. In the past, old Sentani people passed those tales down to teach knowledge, history, entertainment and education for their children and grandchildren. Social values in the tales such as hard work, discipline, persistence, cooperation, love, respect, and helping each other, can be used as media to develop children’s character. Children are prioritized since they are the important pillars who will continue the life of socio-culture in the future. This article is the result of a community service as a dissemination of the previous research, PDUPT 2017/2018 that also encouraged the importance of Sentani folktales as media of children’s charater buiding. The activity is executed in PAUD “Hadassah”, District Heram. Through this activity, it is hoped that pupils and teachers in PAUD Hadassah are enthusiastic to learn Sentani folktales as one of cultural heritages that need to be preserved and disseminated to young generation, especially Sentani children.Keywords: folktales, Sentani people, character education